2019
DOI: 10.1038/s41598-019-40163-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria transfer from mesenchymal stem cells structurally and functionally repairs renal proximal tubular epithelial cells in diabetic nephropathy in vivo

Abstract: The underlying therapeutic mechanism of renal tubular epithelium repair of diabetic nephropathy (DN) by bone marrow-derived mesenchymal stem cells (BM-MSCs) has not been fully elucidated. Recently, mitochondria (Mt) transfer was reported as a novel action of BM-MSCs to rescue injured cells. We investigated Mt transfer from systemically administered BM-MSCs to renal proximal tubular epithelial cells (PTECs) in streptozotocin (STZ)-induced diabetic animals. BM-MSCs also transferred their Mt to impaired PTECs whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 56 publications
3
85
0
4
Order By: Relevance
“…In the kidney, the effectiveness of AMT was demonstrated by rescue of damaged renal proximal tubular cells. In vitro, the administration of MSC-derived mitochondria reduced ROS production and increased the expression of the tubular marker megalin and mitochondrial superoxide dismutase 2, whereas in vivo, both the tubular basement membrane and brush border were protected [61]. Moreover, in normal mice, the administration of mitochondria improved endurance during forced swimming test.…”
Section: Artificial Mitochondria Transfermentioning
confidence: 98%
“…In the kidney, the effectiveness of AMT was demonstrated by rescue of damaged renal proximal tubular cells. In vitro, the administration of MSC-derived mitochondria reduced ROS production and increased the expression of the tubular marker megalin and mitochondrial superoxide dismutase 2, whereas in vivo, both the tubular basement membrane and brush border were protected [61]. Moreover, in normal mice, the administration of mitochondria improved endurance during forced swimming test.…”
Section: Artificial Mitochondria Transfermentioning
confidence: 98%
“…The imbalance of the Bax/Bcl-2 ratio is a feature that often occurs during the process of apoptosis [29]. Mitochondrial transfer from MSCs can reduce apoptosis levels and promote cell viability in recipient cells [30] via regulating the balance of Bax/Bcl-2 and reducing the expression of caspase-3 [31]. Interestingly, transfer of dysfunctional mitochondria from damaged cells to MSCs also has an influence on MSCs.…”
Section: Mitochondrial Transfer Improves Cell Viabilitymentioning
confidence: 99%
“…Experiments demonstrated that mitochondria from BM-MSCs given systematically was transferred into proximal tubular epithelial cells [42], indicating the mitochondria and its relevant functions might occupy a position in the therapeutic effect of MSCs. Mitochondria from MSCs could enhance the expression of superoxide dismutase 2 (SOD2) and Bcl-2 in vitro, inhibiting the production of reactive oxygen species (ROS) and cell apoptosis in PTECs under the condition of high glucose.…”
Section: Inhibition Of Oxidative Stressmentioning
confidence: 99%
“…Mitochondria from MSCs could enhance the expression of superoxide dismutase 2 (SOD2) and Bcl-2 in vitro, inhibiting the production of reactive oxygen species (ROS) and cell apoptosis in PTECs under the condition of high glucose. Besides, megalin and SGLT-2 were also restored to improve blood glucose control and anti-in ammatory effect, especially the reduction of IL-16 [34,42].…”
Section: Inhibition Of Oxidative Stressmentioning
confidence: 99%